Yoghurt Kacang Merah (phaseolus vulgaris l.) Efektif Menurunkan Kadar Kolesterol Total Penderita Hiperkolesterolemia - Eva Yuniritha; Defriani Dwiyanti; Ananta Christyana (Poltekkes Kemenkes Padang, 2022)
Cardiovascular disease is the number one cause of death in the world, one of the factors is hypercholesterolemia which causes thickening of artery walls, resulting in atherosclerosis. The management of hypercholesterolemia is done non-pharmacologically, namely medical nutritional therapy using functional food ingredients, red beans and probiotics containing isoflavones and BAL compounds that can reduce total cholesterol levels. This research aims the effectiveness of giving red bean yoghurt of total cholesterol levels in patients with hypercholesterolemia. This study used a Quasy experiment with pre-post test design, from February 2019 to May 2020 in all patients with hypercholesterolemia in the working area of ​​Nanggalo Public Health Center. The number of samples were 15 cases given red bean yoghurt and 15 controls given 225 mL of probiotic yoghurt for 14 days and were taken by purposive sampling. The data taken is the results of initial and final cholesterol examination of hypercholesterolemia patients, analyzed by T-Test Dependent and Mann Whitney. The results showed an average decrease in total cholesterol levels of respondents given red bean yogurt 40.87 mg/dL and probiotic yogurt 15.47 mg/dL. Statistical test results showed there were significant differences between changes in total cholesterol levels of respondents who were given red bean yoghurt and probiotic yoghurt (p = 0.00). Red bean yoghurt is effective in reducing cholesterol levels so that red bean yogurt can be used as an alternative treatment for cholesterol-lowering.